Electron Emission Characteristics of Multi-gated Field Emitters - Mimura, Hidenori; Neo, Yoichiro; Aoki, Toru; Yoshida, Tomoya; Nagao, Masayoshi (Makara Journal of Technology, 2014)
We have developed a multi-gated field emitter (FE) such as a quadruple-gated FE with a three-stacked electrode lens and a quintuple-gated FE with a four-stacked electrode lens. Both the FEs can focus the electron beam. However, the quintuple-gated FE has a stronger electron convergence than the quadruple-gated FE, and a beam crossover is clearly observed for the quintuple-gated FE.